Computational techniques for modeling non-player characters in games - Feng, Shu (2014)
Modeling of non-player characters (NPCs) is an important research area in the development of computer games. Autonomous NPCs by emulating the behavior of human beings, with realistic performance and believable affective variations, in simulated environment, make the games more challenging and enjoyable.